Bank Competition and Credit Risk: Does Bank Stability moderate the Competition-Credit Risk nexus? - Nepal, Bidush; Gyawali Nepal, Mira (NRB Economic Review, 2025)
This paper intends to understand the impact of bank competition on credit risk and further determine if the association between competition and credit risk depends on bank stability, specifically focusing on commercial banks of Nepal. The study spans from 2011 to 2022 and incorporates various control variables, including macroeconomic, bank-specific, Covid-19 pandemic and regulatory factors. We incorporate a dynamic panel data model and find that while increased competition leads to an increase in credit risks, this effect is reversed in a stable banking environment with strong capitalization, profitability, and steady earnings. Our findings assist policymakers in achieving a more optimal equilibrium between promoting competition and safeguarding financial stability, while also limiting excessive risk-taking. Additionally, it can provide guidance to the bank management in improving their risk management practices.